Intergenerational Social Conflict in Indonesian Migrant Worker Families - Andhita Risko Faristiana (Universitas Pendidikan Ganesha, 2025)
Intergenerational social conflict in Indonesian migrant worker families represents a critical yet underexamined structural phenomenon that fundamentally disrupts family functioning, individual well-being, and cultural value transmission across multiple generations. This systematic literature review aims to comprehensively synthesize empirical evidence on the causal determinants, manifestation patterns, multidimensional impacts, and resolution strategies of intergenerational conflicts in Indonesian migrant worker families between 2020-2025. Following PRISMA guidelines, literature searches were conducted across Scopus, Web of Science, ProQuest, JSTOR, ScienceDirect, and Indonesian repositories (Garuda, Indonesia OneSearch). Initial identification yielded 309 articles; after duplicate removal, screening, and quality appraisal using CASP criteria, 28 high-quality peer-reviewed articles were systematically analyzed using NVivo 12 thematic analysis. Results reveal that conflicts emerge from boundary ambiguity caused by parental absence, communication disruptions intensified by Indonesian